IMPLEMENTASI SAK EMKM PADA UMKM (STUDI KASUS PADA UMKM TEMPE NGRAYUN DI KEBUPATEN PONOROGO) - Mohammad Rudi Ariyanto; Maslichah Maslichah (Universitas Islam Malang, 2022)
Implementation of Financial Accounting Standards for Micro, Small, and Medium Entities carried out at Tempe Ngrayun SMEs in Ngrayun District, Ponorogo Regency using a case study approach with descriptive qualitative methods. Collecting data through interviews directly to the object of research. The implementation of Financial Accounting Standards SMEs in Tempe Ngrayun SMEs is assessed based on four assessment variables, namely accounting records (basic accrual basis and the concept of business entities), ownership of human resources, supporting facilities/infrastructure, and knowledge of Financial Accounting Standards SMEs. The results showed that most of the Tempe Ngrayun SMEs in Ngrayun District, Ponorogo Regency were considered not ready to implement Financial Accounting Standards SMEs. This is based on the interview data obtained showing that all Tempe Ngrayun SMEs have not met the four assessment variables. Almost all SMEs in Tempe Ngrayun can only fulfill one of the assessment variables. The results obtained in this study indicate that the unpreparedness of Tempe Ngrayun SMEs in implementing Financial Accounting Standards SMEs is influenced by the lack of knowledge of Tempe Ngrayun SMEs actors on Financial Accounting Standards SMEs.Keywords: Financial Accounting Standards SMEs, SMEs, Basic Accounting Assumptions, Human Resources, and Supporting Facilities.